Quadruple Quorum-Sensing Inputs Control Group Behaviors in Vibrio cholerae - Jung, Sarah. (2017)
Abstract: Quorum-Sensing (QS) is a microbial cell-to-cell communication process that allows bacteria to function as a collective group and carry out robust, population-wide behaviors that would be ineffective if performed alone. This inter-cellular signaling process relies on cell density-dependent production and detection of chemical signals, called autoinducers (AIs). Many pathogens, including Vibrio cholerae, the causative agent of cholera, depend on QS to regulate important cellular processes essential for adaptation and survival in the environment and within the host during infection. Since its discovery, the V. cholerae QS system has served as a model to understand how bacterial pathogens employ QS for temporal control of virulence factor production. Yet, our understanding of the V. cholerae QS system remains incomplete. V. cholerae detects two well-characterized AIs, CAI-1 and AI-2, with histidine kinase receptors, CqsS and LuxPQ, respectively. At low cell density, these receptors function in parallel to activate the key regulator LuxO, which is essential for virulence of this pathogen. At high cell density, binding of AIs to their respective receptors leads to deactivation of LuxO and repression of virulence factor production. However, mutants lacking CqsS and LuxPQ maintain a normal LuxO activation level and remain virulent, suggesting that LuxO is activated by additional signaling pathways. In this thesis, I define the V. cholerae QS network architecture and examine how and why this pathogen maintains multiple QS inputs. In the first study, I show that two novel histidine kinases, VpsS and CqsR, function in parallel with CqsS and LuxPQ to regulate the V. cholerae QS circuit. In the second study, I examine how QS receptor CqsR senses its signals. In the third study, I investigate why V. cholerae maintains four parallel systems and test how V. cholerae cells resist signal perturbations. Taken together, the results from this thesis suggest that the V. cholerae QS circuit is composed of quadruple sensory inputs and this integration is crucial for eliciting robust and coordinated QS behaviors.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Molecular Microbiology.; Advisors: Wai-Leung Ng, and Paula Watnick.; Committee: Andrew Camilli, Carol Kumamoto, and Ralph Isberg.; Keyword: Microbiology.